Accelerated Failure Time (AFT) model for simulation partly interval-censored data / Ibrahim El Feky and Faiz Elfaki - El Feky, Ibrahim; Elfaki, Faiz (2021)
The performance of maximum likelihood estimators of the parameters of Accelerated Failure Time (AFT) regression model based on Weibull distribution with simple imputations methods under Partly-Interval Censored (PIC) data is studied. The proposed model is tested through the simulation data and the result were compare with semiparametric model. The result indicates that the AFT with Weibull distribution is comparable with Cox model under simulated PIC data via breast cancer data in the present of imputation techniques. In additional to that the result suggested that the parameters of our model are stable, and the treatments are significant for simulated breast cancer patients.